Characterization of proteins, mRNAs, and miRNAs of circulating extracellular vesicles from prostate cancer patients compared to healthy subjects - Chisholm, Jolene; Haas-Neill, Sandor; Margetts, Peter; Al-Nedawi, Khalid (Frontiers in Oncology, 2022)
Prostate cancer (PC) is the fifth leading cause of death in men globally. Measurement of blood PSA level is still considered the gold standard biomarker test for PC, despite its high rate of delivering false positives and negatives that result in an inappropriate medical response, including overtreatment. We collected extracellular vesicles (EV) from the blood plasma of prostate cancer patients with organ-confined, extracapsular-invading, and seminal vesicle-invading tumours, and from healthy subjects. We examined protein, mRNA, and miRNA content of these EV using Mass Spectrometry (MS), a Human Prostate Cancer PCR array, and a miScript miRNA PCR array, respectively. The proteomic analysis showed distinct groups of proteins that are differently expressed in each group of patients, as well as in the healthy subjects. Samples from healthy sub-jects and each tumour type were used for both the mRNA and miRNA arrays. The mRNA analysis showed distinct groups of mRNAs that were overexpressed in the healthy or in one of the three tumour types but not in the EV of the other groups. The miRNA analysis showed distinct groups of miRNAs, as well. The fold of regulation in the expression of the identified mRNA, and miRNA of each stage of the disease from healthy showed that various mRNA, and miRNA could discrim-inate the disease stage. Overall, our data suggest many molecular marker candidates for distin-guishing between healthy subjects and prostate cancer patients using the cargo of circulating vesi-cle, as well as markers to discriminate between the different tumour types. Once verified, these markers might have a diagnostics value for PC.